(untitled) (Journal of Environmental Microbiology and Toxicology, 2025)
This study investigates the adsorption of hexavalent chromium ions (Cr(VI)) onto sugarcane bagasse, employing nonlinear regression to evaluate isothermal models. The experimental data were reanalyzed by converting initial concentrations to equilibrium concentrations (Ce), revealing a monolayer adsorption behavior with a maximum adsorption capacity (Qm) plateauing at 5.75 mg/g. A series of isotherm models was fitted to the data using nonlinear regression, and performance was assessed using multiple error functions. While most models showed good fits, the Koble-Carrigan, Henry, and Dubinin–Radushkevich models were excluded due to poor convergence or high error. The Multiobjective Optimization on the Basis of Ratio Analysis (MOORA) method was employed for model ranking, identifying the Jovanovic, Toth, Redlich–Peterson and Fritz–Schlunder III models as the top performers. The determined maximum adsorption capacity (QmJ) based on the Jovanovic isotherm was found to be 5.84 mg/g, which is very close to the experimental maximum (5.75 mg/g) observed in the experimental data. The binding constant (KJI = 0.02 L/mg) indicates that the affinity was weak. The narrow 95% CI indicates a close fit of the model to the raw data. Despite robust modeling, the limited dataset (n = 8) introduces uncertainty in parameter estimation, underscoring the need for larger datasets. This study also emphasizes MOORA’s potential in adsorption science as an efficient multi-criteria model selection tool.